Gestión presupuestaria en el Gobierno Autónomo Descentralizado Parroquial Rural de Ricaurte, durante el período 2023. - Valero Alfonso, Nelson Yordi (2024)
This case study focused on budget management in the Decentralized Autonomous Rural Parochial Government of Ricaurte, during the period 2023, because it faces important challenges related to financial resource constraints. This problem directly affects the execution of priority projects, the quality of public services and the capacity to respond to critical situations that significantly affect the community. The budget limitation also affects various functions, such as the proper inventory management of the assets belonging to the entity, the ability to meet the proposed objectives and a delay is generated to complete its activities, which generates an unfavorable perspective on the part of citizens regarding the obligations of the institution. Due to this, the comparative analysis method was used to know the budgeted and executed in the corresponding period. The main objective is to identify these problems and thus propose recommendations to strengthen the financial management of the GAD, in order to increase its capacity to meet the demands of the population and promote their general welfare. It is crucial to analyze in detail the distribution of the allocated budget and optimize the available resources. This approach helps to foster a more effective and efficient administration, which is expected to contribute significantly to sustainable development and continuous improvement in the quality of life of the Ricaurteña community.